Metamorphosing Teaching and Learning with Python: A Practical Guide for Teachers Employing Text Data Analysis Using the Bag of Words (BoW) Model - Alam, Ashraf (2023 International Conference on Quantum Technologies, Communications, Computing, Hardware and Embedded Systems Security (iQ-CCHESS), 2023)
This research explores the application of the Bag of Words (BoW) model for text data analysis with the goal of enhancing teaching-learning in the classroom. The BoW model expresses text as a "bag" of its individual words while ignoring word order. The study covers the use of the BoW model toward the creation of intelligent teaching systems. These systems identify areas where students may be having difficulty and offer focused feedback and guidance by examining the language used by students as they work through an issue or subject. The paper uses snippets of Python code as examples and their outputs to demonstrate how the BoW model can be used to improve learning outcomes. The BoW model's importance in assessing educational resources, developing intelligent tutoring programmes, and analysing student writing is greatly emphasised in the paper.